Liothyronine for hypothyroidism: a candidate for disinvestment or in need of further research? A value of information analysis - Dyfrig A Hughes; Pippa Anderson; Adrian Heald; Konstantinos Skiadas (BMJ Open)
Objective Medicines with limited evidence of effectiveness are prime candidates for disinvestment. However, investment in further research may be preferable to deimplementation, given that the absence of evidence is not evidence of absence, and research can inform formulary decisions. A case in point is liothyronine, which is sometimes prescribed to levothyroxine-treated patients who continue to experience hypothyroid symptoms. It is a putative low value medicine, associated with uncertainties in both clinical and cost-effectiveness. The aim was to assess the cost-effectiveness of liothyronine in this context, and estimate the value of conducting further research.Design Cost utility and value of information analyses.Setting Primary care within the National Health Service in the UK.Participants Fifty-four levothyroxine-treated patients with persistent symptoms of hypothyroidism.Interventions Liothyronine plus levothyroxine versus levothyroxine alone.Primary and secondary outcome measures Incremental cost per quality-adjusted life year (QALY) gained, and the expected monetary value of sample information.Results 20/54 (37%) of patients who responded to the survey reported severe problems in carrying out usual activities of everyday living and 12/54 (22%) reported severe anxiety or depression symptoms. Mean (SD) utility was 0.53 (0.23). The differences in expected total, 10-year costs and QALYs between a treatment strategy of liothyronine/levothyroxine combination therapy, and levothyroxine alone, was £12 053 and 1.014, respectively. The incremental cost-effectiveness ratio of £11 881 per QALY gained was sensitive to the price of liothyronine. The probability of liothyronine/levothyroxine combination therapy being cost effective at a threshold of £20 000 per QALY was 0.56. The value of reducing uncertainty in the efficacy of treatment was £3.64 m per year in the UK.Conclusions A definitive clinical trial to confirm clinical effectiveness may be preferable to immediate disinvestment, and would be justified given the value of the information gained far exceeds the cost.